Effect of External Surface Diffusion Barriers on Platinum/Beta‐Catalyzed Isomerization of n‐Pentane. Issue 26 (17th May 2021) - Hu, Shen; Liu, Junru; Ye, Guanghua; Zhou, Xinggui; Coppens, Marc‐Olivier; Yuan, Weikang
Abstract: We have developed a generalizable strategy to quantify the effect of surface barriers on zeolite catalysis. Isomerization of n‐pentane, catalyzed by Pt/Beta, is taken as a model reaction system. Firstly, the surface modification by chemical liquid deposition of SiO2 was carried out to control the surface barriers on zeolite Beta crystals. The deposition of SiO2 leads to a very slight change in the physical properties of Beta crystals, but an obvious reduction in Brønsted acid sites. Diffusion measurements by the zero‐length column (ZLC) method show that the apparent diffusivity of n‐pentane can be more than doubled after SiO2 deposition, indicating that the surface barriers have been weakened. Catalytic performance was tested in a fixed‐bed reactor, showing that the apparent catalytic activity improved by 51–131 % after SiO2 deposition. These results provide direct proof that reducing surface barriers can be an effective route to improve zeolite catalyst performance deteriorated by transport limitations. Abstract : External surface diffusion barriers on zeolite Beta crystals significantly reduce their apparent catalytic activity in catalyzing isomerization of n ‐pentane. Eliminating surface barriers can lead to an improvement in apparent catalytic activity higher than 131 %.